Central versus Local Education Finance: A Political Economy Approach - Rainald Borck (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper models voters' preferences over central versus local education policies when there are private alternatives. Education is financed by income taxes and individuals are mobile between communities. Public education levels are chosen by majority vote. Contrary to conventional wisdom, centralisation may benefit the rich and poor, while the middle class prefer decentralised education. The model is also extended to include peer effects. Peer effects increase the support for central school finance, even in the community with good public schools.
Keywords: I22; D72; H72; 330; education; centralisation; private schools; majority voting